2014
DOI: 10.5688/ajpe78596
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Online Versus Classroom Delivery of an Immunization Elective Course

Abstract: Objective. To compare performance and preferences of students who were randomly allocated to classroom or online sections of an elective course on immunization. Methods. Students were randomly assigned to either the classroom or online section. All course activities (lectures, quizzes, case discussions, vaccine administration, and final examination) were the same for both sections, except for the delivery of lecture material. Assessment. Students were surveyed on their preferences at the beginning and end of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 17 publications
7
46
2
Order By: Relevance
“…However, very little literature has yet examined whether student learning outcomes in online counselor education programs are equivalent to their traditional, on-campus equivalents (Meder, 2013). Overall, current literature shows positive trends that support the use of online learning in higher education, although some of this research is based on an undergraduate learning experience (Chang & Chen, 2014;Frimming et al, 2013;Porter et al, 2014;Russell, 2001). However, research within the counseling field has shown positive results regarding student perception of this learning modality (Blackmore et al, 2008;Ting & Gonzalez, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, very little literature has yet examined whether student learning outcomes in online counselor education programs are equivalent to their traditional, on-campus equivalents (Meder, 2013). Overall, current literature shows positive trends that support the use of online learning in higher education, although some of this research is based on an undergraduate learning experience (Chang & Chen, 2014;Frimming et al, 2013;Porter et al, 2014;Russell, 2001). However, research within the counseling field has shown positive results regarding student perception of this learning modality (Blackmore et al, 2008;Ting & Gonzalez, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A vast array of studies has been conducted in other fields, consistently showing no significant differences in student learning outcomes when online courses, hybrid courses, and on-campus courses are compared (Russell, 2001;Summers et al, 2005). Across undergraduate disciplines, online learning has been shown to be a sufficient learning environment for students in terms of learning outcomes and knowledge retention (Chang & Chen, 2014;Frimming, Bower, & Choi, 2013;Porter et al, 2014). Summers et al (2005) compared learning outcomes for undergraduate nursing students taking online or on-campus versions of a statistics course.…”
Section: Online Teaching and Learningmentioning
confidence: 99%
“…[10][11][12][13][14][15] In addition to homegrown activities, a number of colleges/schools offer the APhA immunization training program, an approved certificate course for pharmacists who plan to engage in vaccination. 16 Although the APhA program is not allinclusive and the vast majority of colleges/schools continue to integrate immunization education into their required/core curricula, this certificate program now appears to be the standard way in which colleges/schools are educating students on the topic of immunization: This program is overseen by experts in the field, provides a standardized way in which pharmacists are trained, incorporates activelearning components, and requires demonstration of competency through a post-examination and via demonstration of vaccination technique.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] The manner in which and the extent to which this topic is taught at US colleges and schools of pharmacy is unknown, but based on a variety of published reports, appears to vary across the country. [10][11][12][13][14][15][16] The primary objective of this study was to determine the extent to which immunization is taught at US colleges/schools of pharmacy and secondarily, to characterize what immunization/vaccinerelated content is being taught.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that classroom participation increased and students perceived increased levels of support from fellow classmates (Ebner, Lienhardt, Rohs, & Meyer, 2009). Across disciplines, numerous studies have compared face-to-face courses and online courses with regard to student results and knowledge retention, which have consistently showed no significant difference in learning outcomes (Chang & Chen, 2014;Frimming, Bower, & Choi, 2013;Porter, Pitterle, & Hayney, 2013).…”
Section: Call For Technology In Higher Educationmentioning
confidence: 99%